Peroxidase inactivation kinetics is affected by the addition of calcium chloride in fruit beverages - Kubo M.T.K. (2018)
The authors are grateful to the National Council for Scientific and Technological Development (CNPq, Brazil) for funding the project no 401004/2014–7 and M.T.K. Kubo PhD scholarship (233347/2014-3), and Cienciactiva from the “Consejo Nacional de Ciencia, Tecnología e Inovación Tecnológica” (CONCYTEC, Peru) for the M.L.Rojas PhD scholarship (Contract 087-2016-FONDECYT).